2004
DOI: 10.1562/0031-8655(2004)080<0412:peovlo>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Phototoxic Effect of Visible Light on Porphyromonas gingivalis and Fusobacterium nucleatum: An In Vitro Study¶†

Abstract: The antibacterial effect of visible light irradiation combined with photosensitizers has been reported. The objective of this was to test the effect of visible light irradiation without photosensitizers on the viability of oral microorganisms. Strains of Porphyromonas gingivalis, Fusobacterium nucleatum, Streptococcus mutans and Streptococcus faecalis in suspension or grown on agar were exposed to visible light at wavelengths of 400-500 nm. These wavelengths are used to photopolymerize composite resins widely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 27 publications
4
39
1
Order By: Relevance
“…The red LED irradiation (135 J/cm 2 ) did not lead to any differences in the bacterial cells compared to the non‐irradiated control in terms of their growth. In contrast, blue LED irradiation (135 J/cm 2 ) delayed the growth of P. gingivalis , which was in agreement with the results of previous studies 9, 20–23, 28, 29. However, the molecular mechanisms underlying the effects of blue light/LED exposure on bacterial growth were unclear with regard to whether blue light/LED light actually kills bacteria or only inhibits their growth.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The red LED irradiation (135 J/cm 2 ) did not lead to any differences in the bacterial cells compared to the non‐irradiated control in terms of their growth. In contrast, blue LED irradiation (135 J/cm 2 ) delayed the growth of P. gingivalis , which was in agreement with the results of previous studies 9, 20–23, 28, 29. However, the molecular mechanisms underlying the effects of blue light/LED exposure on bacterial growth were unclear with regard to whether blue light/LED light actually kills bacteria or only inhibits their growth.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, there have been many reports about the effects of LED on bacteria. Red light or near infrared light was reported to exert no antimicrobial effects 18–20. In contrast, blue light has been reported to possess a bactericidal effect; the delivery of blue light (representing 15–58.8 J/cm 2 energy density) is sufficient to reduce the viability of bacteria such as H. pylori 9, methicillin‐resistant Staphylococcus aureus 21, Pseudomonas aeruginosa , and S. aureus 22.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…BL at a wavelength of 405 nm (15 J/cm 2 ) achieved reduction rates of 95.1% and nearly 90% for Pseudomonas aeruginosa and S. aureus , respectively . Regarding periodontal pathogens, BL at 94 J/cm 2 (3 min) reduced the survival rates of P. gingivalis and Fusobacterium nucleatum by 90% and 40%, respectively . Moreover, BL irradiation at 4.2 J/cm 2 (1 min) resulted in complete killing of Prevotella intermedia and Prevotella nigrescens , and irradiation at 42 J/cm 2 (10 min) reduced P. gingivalis by 98.5% .…”
Section: Discussionmentioning
confidence: 91%
“…On BL irradiation, it has been speculated that endogenous porphyrin produced by bacteria is excited, leading to a photodynamic reaction through singlet oxygen production, resulting in an antimicrobial effect . In contrast, some in‐vitro studies reported that red light or near‐infrared light exerted no antibacterial effect .…”
Section: Discussionmentioning
confidence: 99%